VERBS MEANING NEGATIVE ATTENDING CIRCUMSTANCES IN THE MODERN RUSSIAN LANGUAGE: SYSTEMATIC AND FUNCTIONAL ASPECTS - Van Cyan (Гуманитарные и юридические исследования)
The article is devoted to the verbs of the mode of action in which excessiveness and duration are combined with negative consequences. This combination of excessiveness and duration with negative result of the action is characteristic of a number of pre-fixed-postfixed and purely prefixed modes of action. The article studies functioning of these verbs in ictional texts, contextual and situational conditions of their realization are analyzed as well. It is speciied that in some modes of action the semantics of negative consequences is expressed more explicitly, markedly, while in others it is implicit, covert. The semantics of negative action consequences is mostly expressed by conixal verbs which concentrating the action on the sphere of subject mean excessive activity of the subject in performing actions resulting in negative consequences. Verbs meaning negative result of the action are very expressive and stylistically colored, as a rule. They often have one aspect - perfective, though imperfective forms are also possible if they express multiplicity. Such verbs are drawn to perfective forms because semantics of excessiveness, satiety and extremity of action is mostly associated with perfective aspect which points out the fact of the action, not its process . The analysis of the above mentioned modes of action bearing a complex of meanings allows us to draw some conclusions about the peculiarities of the Russian vision of the world, Russian character and outlook.